Tourisme et crises sanitaires mondiales dans l’Histoire : véritablement un impensé ? - Evanno, Yves-Marie; Vincent, Johan (Mondes du tourisme, 2021)
Traveling around the world is not a risk-free activity. While the influence of natural hazards, military conflicts, and social tensions on international tourism is relatively well known, health risks on tourism are still not properly understood. The Covid-19 pandemic, described as “unprecedented” for the tourism sector, has highlighted this historiographic gap that we wish to begin to fill with a long-term approach, beyond the 21st century disease episodes (SARS, avian flu, swine flu, MERS.). While disease was perceived as the consequence of a bad environment until the 19th century, several cholera pandemics prove that even places that were thought to be preserved, allowing for health tourism, can be affected. The management of pandemics raises awareness about the respectability of territories. In the early 20th century, the control of medical risks – at least in Western countries – continued to improve, with death becoming more a matter of “statistical bad luck”. However, with the rise of rapid transportation and the close contact with exotic destinations, the tourist once again became a possible carrier of the disease. In the field of tourism, crisis management is therefore intended to be global, although in reality it remains the responsibility of local actors. Voyager à travers le monde n’est pas une activité sans risques. Si l’influence des aléas naturels, des conflits militaires ou encore des tensions sociales sur le tourisme international est relativement bien connue, il n’en va pas de même pour les risques sanitaires. La Covid-19, qualifiée de « sans précédent » pour le secteur touristique, a mis en évidence cette lacune historiographique, que cet article tente de commencer à combler par une approche sur le temps long, au-delà des seuls épisodes du xxie siècle (SRAS, grippe aviaire, grippe porcine, MERS…). Alors que la maladie est perçue comme la conséquence d’un mauvais environnement jusqu’au xixe siècle, plusieurs pandémies de choléra prouvent que même les lieux que l’on pensait alors préservés, ...